Potential of Chlorella sp. grown in wastewater on the growth and yield of Amaranthus sp. - Saththivel, P.; Jeyakumar, K.; Gnanavelrajah, N.; Ketheesan, B. (Sabaragamuwa University of Sri Lanka, 2022)
Global usage of chemical fertilizer has been increasing over the last three decades to meet the food demand due to the growing population. Consequently, this can lead to soil degradation (Shaaban et al., 2010). Organic fertilizer is a good alternative to inorganic fertilizers as it is an environmentally sound as well as economically viable option. Due to the present covid-19 situation, readily available organic fertilizers are limited. To counteract the current issues, biofertilizer has become the best alternative solution. Biofertilizer, a new tear that’s being used widely nowadays to enrich the soil with microalgae, bacteria, and fungi that promote the growth and yield of crops (De Jesus Raposo & De Morais, 2011). Microalgae biomass is one of the sources of biofertilizer. Chlorella sp. can be cultivated for biofertilizer production, which provides a high amount of macro and micronutrients, metabolites like protein, carbohydrates, and constituents, and growth-promoting substances such as cytokinin (Dineshkumar et al., 2020). In Sri Lanka, there is an increasing trend for consuming leafy vegetables to obtain nutrients, especially micronutrients. Dark leafy vegetables are preferred due to the rich sources of vitamins such as A and C; minerals calcium, iron, and phosphorous; antioxidants and phytochemicals. Amaranthus is one of them and is highly cultivated in Sri Lanka (Nadeeshani et al., 2018). As Chlorella sp. is an aquatic organism it demands water for its growth. However, wastewater could be used to supplement nutrients as well as to replace freshwater to grow Chlorella sp. The objective of this study was to assess the potential of Chlorella sp. grown in parboiled effluent on the growth and yield of Amaranthus sp.